CardCaptor Sakura - Collector's Edition I - CLAMP (Mangaka group); Igarashi, Satsuki; Okawa, Nanase, 1967-; Nekoi, Tsubaki, 1969-; Onishi, Mika; Sengupta, Anita; CLAMP (Mangaka group). (New York : Kodansha Comics, an imprint of Kodansha USA Publishing, LLC, 2019)
"The adventures of the plucky Sakura Kinomoto are as adorably thrilling as ever, as she tracks down the magical Clow Cardsand plunges headlong into a world of sorcery beyond anything she couldve imagined"--Provided by publisher.
"A Kodansha Comics Original"--Colophon.
"T, ages 13+"--Back cover.
Keywords: Middle school students -- Comic books, strips, etc; Juvenile fiction; Magic -- Comic books, strips, etc; Juvenile fiction; Middle school students -- Juvenile fiction; Magic -- Juvenile fiction; Fantasy comics; Graphic novels